The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0974-2069.132475
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive estimation of pulmonary vascular resistance in patients of pulmonary hypertension in congenital heart disease with unobstructed pulmonary flow

Abstract: Context:Pulmonary vascular resistance (PVR) is a critical and essential parameter during the assessment and selection of modality of treatment in patients with congenital heart disease accompanied by pulmonary arterial hypertension.Aim:The present study was planned to evaluate non-invasive echocardiographic parameters to assess pulmonary vascular resistance.Settings and Design:This prospective observational study included 44 patients admitted in the cardiology and pediatric cardiology ward of our institution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…However, their measurement required two sets of Doppler recording: (1) during tricuspid regurgitation and (2) systolic pulmonary flow. In fact, all Doppler based methods have yielded similar results (21-26) with the same major limitation: the need to measure tricuspid regurgitation hemodynamics. Measurable tricuspid regurgitation Doppler envelopes may not be present in normotensive patients, PH patients with modestly elevated pressures, or in patients with poor acoustic windows due to body habitus.…”
Section: Discussionmentioning
confidence: 99%
“…However, their measurement required two sets of Doppler recording: (1) during tricuspid regurgitation and (2) systolic pulmonary flow. In fact, all Doppler based methods have yielded similar results (21-26) with the same major limitation: the need to measure tricuspid regurgitation hemodynamics. Measurable tricuspid regurgitation Doppler envelopes may not be present in normotensive patients, PH patients with modestly elevated pressures, or in patients with poor acoustic windows due to body habitus.…”
Section: Discussionmentioning
confidence: 99%
“…The TRV/RVOT VTI ratio has recently been shown to correlate well with PVR measured at catheterization in pediatric PH patients. 44 Pande et al 44 showed that, in this pediatric cohort (mean age: 9.7 years), the TRV/RVOT VTI ratio value of 0.14 provided a sensitivity of 96% and a specificity of 93% for a PVR of 6 Wood units. Normative pediatric RVOT VTI values were recently published.…”
Section: Trv/rvot Velocity Time Integral (Vti) Ratiomentioning
confidence: 99%
“…TRV:VTI [RVOT] ratio have been shown to correlate well with PVR in children and a cut off value of 0.14 provided high predictive values. 34 However, neonatal studies are lacking.…”
Section: Echocardiographymentioning
confidence: 99%